Determinants of Potential Investment Attractiveness of a Commune - Świdyńska, Natalia; De Jesus, Ilisio Manuel (Olsztyn Economic Journal, 2020)
The aim of the study was to indicate which of the determinants shaping the level of potential investment attractiveness of a commune affects its level to the highest degree. The elements which determine the attractiveness for investment, understood as an area’s ability to attract investors, were classified into five sections: labour resources, technical infrastructure, social infrastructure, administration and market. After the data were accumulated which were necessary to create synthetic indices of communes potential attractiveness for investment and individual sections, they were verified statistically according to two most important criteria: variance and correlation. Ultimately, indices were selected for further analysis out of the set of 39 indices. The Hellwig development pattern method was used to classify the communes into four classes depending on the level of potential attractiveness for investment and each section and to determine which element has the greatest effect on the level of a commune’s potential attractiveness for investment. The average level of potential attractiveness for investment and the sections under analysis prevailed in the Warmińsko-Mazurskie Voivodship communes in 2016. The results showed that the level of a commune’s potential attractiveness for investment is affected by the following factors: technical infrastructure, administration, social infrastructure, labour resources and market.